2022
DOI: 10.1001/jamaoto.2021.2769
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Conduction Devices for Single-Sided Sensorineural Deafness With Quality of Life

Abstract: IMPORTANCEAlthough bone conduction devices (BCDs) have been shown to improve audiological outcomes of patients with single-sided sensorineural deafness (SSD), their effects on the patients' quality of life (QOL) are unclear.OBJECTIVE To investigate the association of BCDs on QOL in patients with SSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Greater improvement in the speech-hearing subscale reflected WRS improvement. A meta-analysis of the effects of BCDs on the quality of life of patients with SSD concluded that BCDs improved the Abbreviated Profile of Hearing Aid Benefits and the SSQ but not the Health Utilities Index-3 (Hampton et al, 2022). In the same study, the mean difference was 2.03 for speech and 1.51 for spatial hearing, indicating a greater improvement than that obtained in the present study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Greater improvement in the speech-hearing subscale reflected WRS improvement. A meta-analysis of the effects of BCDs on the quality of life of patients with SSD concluded that BCDs improved the Abbreviated Profile of Hearing Aid Benefits and the SSQ but not the Health Utilities Index-3 (Hampton et al, 2022). In the same study, the mean difference was 2.03 for speech and 1.51 for spatial hearing, indicating a greater improvement than that obtained in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Patients with SSD often have worse sound localization abilities and speech recognition difficulties in noisy and other challenging listening situations due to the loss of binaural processing (Welsh et al, 2004;Yu, 2020). The use of BCDs by patients with SSD improves speech perception and provides subjective benefits (Pfiffner et al, 2009;Wazen et al, 2010;Wesarg et al, 2013;Hampton et al, 2022;Huber et al, 2022). Their effects on speech discrimination in noise have been controversial and dependent on the signal setting and noise direction; however, a systematic review that assessed the efficacy of bone-anchored hearing aids (BAHAs) concluded they have favorable effects based on speech discrimination in noisy circumstances (Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is believed that stimulation of the contralateral auditory pathway may play an important role in suppressing experienced tinnitus [71]. Regarding the effects of BCD on QoL, a recent systematic review and meta-analysis found that BCD are associated with significant improvements in hearingrelated QoL as measured by the APHAB (Abbreviated Profile of Hearing Aid Benefit) https://harlmemphis.org/abbreviated-profile-of-hearing-aid-benefit-aphab/ (accessed on 10 January 2024) and SSQ (Speech, Spatial, and Qualities of Hearing Scale) scores in adult patients, while no difference was found in generic measures of QoL as measured by the HUI-3 (Health Utilities Index-3) [72].…”
Section: Bone Conduction Devices (Bcd): Surgically Implanted Devicesmentioning
confidence: 99%